The Governor's Residence, Trinidad, B.W.I. - (:unkn) unknown (Muir Marshall and Co., 2009)
A picture of a giant Samaan tree in the gardens of the Governor's residence partially shading one side of the main building. Today this residence is known as "The President's House".
Colour: Sepia; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Public buildings--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Gardens--Trinidad and Tobago; Trees--Trinidad and Tobago; Architecture--Trinidad and Tobago; President's House, The